From the lesson tee to the course: a naturalistic investigation of attentional focus in elite golf - Orr, S.; Cruickshank, A.; Carson, H. J. (The Sport Psychologist, 2021)
While debate continues on "optimal" attentional focus, little empirical knowledge exists on the way that attention is operationalized across training and performance in elite golf. Accordingly, this study aimed to (a) explore the attentional foci promoted or used by coaches and players for different types of shots in training, plus their underpinning rationale and (b) explore the attentional foci promoted or used by coaches and players in competition, plus their underpinning rationale. Our findings revealed that (a) various foci were used across training and competition; (b) all players used different combinations of foci across training and competition, and within different aspects of training itself (e.g., short vs. long game); and (c) players often used alternative or additional foci in training to those promoted by coaches, and self-generated foci for competition. These results highlight the complexity and practical reality that needs to underpin future advances in theory, research, and practice.